MODEL PEMBELAJARAN DRIBBLING PADA PERMAINAN SEPAKBOLA UNTUK SISWA SEKOLAH MENENGAH PERTAMA - Iqbal Jasri; Firmansyah Dlis; Hidayat Humaid (Program Studi Pendidikan Jasmani, STKIP Bina Bangsa Getsempena, 2018)
The goal to be achieved from this research and development is to produce dribbling learning model product on football game for junior high school students. This research and development is conducted to be able to obtain information about the development and application of dribbling learning model on the game of football for junior high school students and to know the effectiveness of the resulting model. This research uses Research & Development (R & D) method from Borg and Gall. Subjects in this study were junior high school students consisting of 40 students. The steps in this study are: needs analysis, expert evaluation (initial product evaluation), small group trial, and field testing. Test the effectiveness of the model using soccer dribbling skills test used to determine the level of dribbling ability of students before and after giving treatment dribbling learning model developed. Initial test done obtained level of dribbling ability of student is 3,236 second. After given treatment dribbling learning model obtained level of dribbling ability students 9.736 seconds. On the significant test the difference with spss 16 obtained mean = -6.500 shows the difference of pre-test results and post-test results, t-count = -28.429 df = 37 and p-value = 0.00 <0.05 which means there is a significant difference between before and after given the treatment of dribbling learning model on the game of football. Thus a dribbling learning model on football games for junior high school students is effective to improve dribbling skills in football games for Junior High School Students. Abstrak Tujuan yang ingin dicapai dari penelitian dan pengembangan ini adalah untuk menghasilkan produk model pembelajaran dribbling pada permainan sepakbola untuk siswa SMP. Penelitian dan pengembangan ini dilakukan untuk dapat memperoleh informasi tentang pengembangan dan penerapan model pembelajaran dribbling pada permainan sepakbola untuk siswa SMP serta untuk mengetahui efektivitas model yang dihasilkan. Penelitian ini menggunakan metode Research & Development (R&D) dari Borg and Gall. Subyek dalam penelitian ini adalah siswa SMP yang terdiri dari 40 siswa. Tahapan-tahapan dalam penelitian ini adalah : analisis kebutuhan, evaluasi ahli (evaluasi produk awal), ujicoba kelompok kecil, dan ujicoba kelompok besar ( field testing). Uji efektivitas model menggunakan tes keterampilan dribbling sepakbola yang digunakan untuk mengetahui tingkat kemampuan dribbling siswa sebelum dan sesudah pemberian perlakuan model pembelajaran dribbling yang dikembangkan. Tes awal yang dilakukan diperoleh tingkat kemampuan dribbling siswa adalah 3.236 detik. Setelah diberikan perlakuan model pembelajaran dribbling didapatkan tingkat kemampuan dribbling siswa 9.736 detik. Pada uji signifikan perbedaan dengan spss 16 didapatkan mean= -6.500 menunjukan selisih dari hasil pre-test dan hasil post-test, hasil t-hitung= -28.429 df=37 dan p-value= 0.00 < 0.05 yang berarti terdapat perbedaan yang signifikan antara sebelum dan sesudah diberikan perlakuan model pembelajaran dribbling pada permainan sepakbola. Dengan demikian model pembelajaran dribbling pada permainan sepakbola untuk siswa SMP efektif untuk meningkatkan kemampuan dribbling pada permainan sepakbola untuk Siswa SMP. Kata Kunci : Model, latihan, sepakbola, dribbling